Career guidance system for secondary school students / Rabiatul Adawiyah Ismail - Ismail, Rabiatul Adawiyah (2006)
This research project is about developing career guidance system for secondary school students. The objectives of this research are to acquire knowledge of conventional way of conducting career guidance in secondary schools, to design career guidance system for secondary school students and to develop career guidance system for secondary school students in Malaysia. The methods used in tiie development of this project require interviewing of career guidance expert and guidance teachers and reviewing similar systems on the Internet. The information obtained from these two approaches was subsequently analyzed. The possibility of this system to be useful to secondary school students is high because all the critical functions and important features which must be provided to them are included in the system as suggested by the career expert and guidance teacher.